2021
DOI: 10.1021/acs.organomet.1c00228
|View full text |Cite
|
Sign up to set email alerts
|

Directing Selectivity to Aldehydes, Alcohols, or Esters with Diphobane Ligands in Pd-Catalyzed Alkene Carbonylations

Abstract: Phenylene-bridged diphobane ligands with different substituents (CF3, H, OMe, (OMe)2, tBu) have been synthesized and applied as ligands in palladium-catalyzed carbonylation reactions of various alkenes. The performance of these ligands in terms of selectivity in hydroformylation versus alkoxycarbonylation has been studied using 1-hexene, 1-octene, and methyl pentenoates as substrates, and the results have been compared with the ethylene-bridged diphobane ligand (BCOPE). Hydroformylation of 1-octene in the prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…As a model reaction, we studied the carbonylation of 1‐octene in the presence of nonanoic acid, in order to produce the symmetric anhydride, nonanoic anhydride (Table 1). 1‐Octene is widely been used in carbonylation reactions, including hydroformylation [23–28] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a model reaction, we studied the carbonylation of 1‐octene in the presence of nonanoic acid, in order to produce the symmetric anhydride, nonanoic anhydride (Table 1). 1‐Octene is widely been used in carbonylation reactions, including hydroformylation [23–28] …”
Section: Resultsmentioning
confidence: 99%
“…1-Octene is widely been used in carbonylation reactions, including hydroformylation. [23][24][25][26][27][28] We found that an initial catalyst system consisting of Pd(OAc) 2 , PPh 3 and trifluoroacetic acid is capable of catalyzing the Reppe-carbonylation of 1-octene with nonanoic acid in the presence of 50 bar CO (Entry 1). In order to optimize the catalyst concentration, the effect of the Pd loading (0.2-1 mol %) on the yield of the nonanoic anhydride was investigated (Entries 1-3), while keeping the ratio of Pd:PPh 3 (1 : 20) and Pd:TFA (1 : 40) constant.…”
Section: Catalyst Development and Optimizationmentioning
confidence: 99%
“…Heterocyclic phosphines offer unique properties that can be tuned by ring size, substituents and functional groups 20 23 . In order to access more ligands incorporating bulky phosphinanes, we targeted the synthesis of the secondary phosphine synthon, TMPhos.…”
Section: Introductionmentioning
confidence: 99%
“…17 We have been interested in developing new routes to bulky diphosphine ligands, as some of these have proved effective at Pd-catalysed isomerising carbonylation reactions. 2,18…”
Section: Introductionmentioning
confidence: 99%